Texture classification using ART-based neural networks and fractals - Kasparis, Takis; Charalampidis, Dimitrios; Georgiopoulos, Michael N. (My University, 1998)
In this paper texture classification is studied based on the fractal dimension (FD) of filtered versions of the image and the Fuzzy ART Map neural network (FAMNN). FD is used because it has shown good tolerance to some image transformations. We implemented a variation of the testing phase of Fuzzy ARTMAP that exhibited superior performance than the standard Fuzzy ARTMAP and the 1-nearest neighbor (1-NN) in the presence of noise. The performance of the above techniques is tested with respect to segmentation of images that include more than one texture.
Keywords: Classification; Fractals; Computer vision; Neural networks